Persepsi masyarakat terhadap pembuatan gigi tiruan pada tukang gigi di kecamatan grogol petamburan jakarta barat - Wirahadikusumah, Andy; Rainy Soenoe, Hanna (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: In cases of tooth loss, prosthodontic treatment can be carried out to replace missing teeth by making artificial teeth. Dentures function to restore chewing, speaking and aesthetic function. In general, to fulfill the need for making dentures, people can choose to visit a dentist or dental technician. Each individual's perception of making dentures by a dentist can be influenced by various things. Objectives: To determine the public's perception of making dentures by dentists in the Grogol Petamburan sub-district, West Jakarta. Methods: Descriptive observational study with a cross-sectional design involving 110 respondents. Data collection uses a questionnaire via Google Form which has been tested for validity and reliability. Results: It was found that the majority of respondents aged 20-30 years were 59 people (53.6%), 86 people were female (78.2%), the majority had tertiary education as many as 59 people (53.6%) and high school as many as 45 people (40.9%), and the majority did not use dentures, 87 people (79.1%). The public's perception regarding needs is categorized as very necessary as many as 43 people (39.1%), the public's perception regarding competence is categorized as incompetent as many as 39 people (35.5%), the public's perception regarding costs is categorized as cheap is 42 people (38.2%), and the public's perception of time is categorized as fast as many as 40 people (36.4%). Conclusion: Dentists are good at meeting the needs of people who have lost the function of mastication, speech, beauty and self-confidence, but are not competent in doing so. And compared to a dentist, making dentures from a dentist requires cheaper costs with a faster manufacturing time.